Secure IT Systems: 21st Nordic Conference, NordSec 2016, Oulu, Finland, November 2-4, 2016. Proceedings - Brumley, Billy Bob; Röning, Juha (LNCS sublibrary. SL 4, Security and cryptology, 2016)
This book constitutes the proceedings of the 21st Nordic Conference on Secure IT Systems, held in Oulu, Finland, in November 2016. The 16 full papers presented in this volume were carefully reviewed and selected from 43 submissions.The focus of the conference is on following topics: Security, System Security, Network Security, Software Security, and Information Security.<data security, mobile="" security, security="" protocols, risk="" management, security="" models,="" and vulnerability="">